In Situ Swelling-Gated Chemical Sensing Actuator - Fushun Wang; Baoguo Chen; Lei Wu; Qiuhua Zhao; Lidong Zhang (Cell Reports Physical Science, 2020)
Summary: Stimuli-responsive elastic organogels have a potential for functional sensors and actuators. However, it remains a challenge to prepare an organogel actuator that can be driven by in situ swelling to generate controlled shape morphing and maintain its kinematic activities with consecutive sorption/desorption of organic solvents. Here, we report a stretchable (strain, 130%), robust (stress, 7.0 MPa), and elastic organogel that is synthesized through ring-opening polymerization of a long-chain epoxide monomer into a crosslinking fluoro-network (CFN). The structure results in the organogel being capable of absorbing polar organic solvents (maximum swellability: 178% ± 10%) and generating indefatigable shape morphing. The in situ swelling (no diffusion) of organic droplets can induce shape morphing in a controllable manner, without the assistance of any structural designs, such as surface patterning, bilayer structures, and origamis. A series of kinematics tests demonstrate that the CFN organogel has a potential for chemical sensing devices.